2023
DOI: 10.3390/v15091964
|View full text |Cite
|
Sign up to set email alerts
|

Clematis vitalba Is a Natural Host of the Novel Ilarvirus, Prunus Virus I

Pal Salamon,
Zsuzsanna Nagyne-Galbacs,
Emese Demian
et al.

Abstract: Clematis vitalba L. is a climbing shrub and a pioneer plant in abandoned orchards or vineyards that are widespread in temperate climate zones. In past years, several viruses infecting the Clematis species have been identified, including different ilarviruses. Prunus virus I (PrVI) is a recently described ilarvirus, which has been shown to infect sweet cherries and peaches in Greece. Moreover, its presence has been detected in ornamental Clematis in Russia. In the present work, we analyzed the virome of wildly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The recent discovery of PrVI in Italy described in the present study, although associated with different symptoms in C. vitalba plants from those described on the same host by previous authors (Chirkov et al, 2022;Salamon et al, 2023), confirms that this plant is an important natural host for this virus. Since PrVI was only recently described, it is not clear what is its diffusion in nature or its impacts on cultivated plants.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The recent discovery of PrVI in Italy described in the present study, although associated with different symptoms in C. vitalba plants from those described on the same host by previous authors (Chirkov et al, 2022;Salamon et al, 2023), confirms that this plant is an important natural host for this virus. Since PrVI was only recently described, it is not clear what is its diffusion in nature or its impacts on cultivated plants.…”
Section: Resultssupporting
confidence: 87%
“…Using HTS analysis, PrVI was first described on asymptomatic sweet cherry (Prunus avium) in Greece (Orfanidou et al, 2021), but was subsequently identified in the weed plant P. echioides (Rivarez et al, 2022) and repeatedly in Clematis spp. plants, mainly in Eastern Europe, including Hungary, Slovenia, Slovakia, Croatia and Russia (Chirkov et al, 2022;Rivarez et al, 2022;Salamon et al, 2023).…”
Section: Resultsmentioning
confidence: 99%